Island extinctions: processes, patterns, and potential for ecosystem restoration - WOOD, JAMIE R.; ALCOVER, JOSEP A.; BLACKBURN, TIM M.; BOVER, PERE; DUNCAN, RICHARD P.; HUME, JULIAN P.; LOUYS, JULIEN; MEIJER, HANNEKE J.M.; RANDO, JUAN C.; WILMSHURST, JANET M. (Environmental conservation, 2017)
Extinctions have altered island ecosystems throughout the late Quaternary. Here, we review the main historic drivers of extinctions on islands, patterns in extinction chronologies between islands, and the potential for restoring ecosystems through reintroducing extirpated species. While some extinctions have been caused by climatic and environmental change, most have been caused by anthropogenic impacts. We propose a general model to describe patterns in these anthropogenic island extinctions. Hunting, habitat loss and the introduction of invasive predators accompanied prehistoric settlement and caused declines of endemic island species. Later settlement by European colonists brought further land development, a different suite of predators and new drivers, leading to more extinctions. Extinctions alter ecological networks, causing ripple effects for islands through the loss of ecosystem processes, functions and interactions between species. Reintroduction of extirpated species can help restore ecosystem function and processes, and can be guided by palaeoecology. However, reintroduction projects must also consider the cultural, social and economic needs of humans now inhabiting the islands and ensure resilience against future environmental and climate change.